Women's Struggle : A History of the All India Women's Conference 1927-2016 (Third Edition) - Basu, Aparna, (Brill | Manohar Publishers & Distributors, 2018)
The All India Women's Conference completed ninety years in 2017. The first edition of this book was brought out in 1990 when it had completed sixty years. The volume was widely appreciated as little work had been done on the history of women's organizations and their contribution to women's development. A second edition was published when AIWC celebrated its Platinum Jubilee in 2002-3. These editions were cited in numerous books and articles in journals of women's history in India and abroad. This third edition carries the story of AIWC forward for little over a decade from 2002-3 onwards. Founded in 1927 in Poona, AIWC's main goal initially was promoting women's education. But it soon took up issues of social legislation and social reform. There has been continuity and change in the activities and programmes of AIWC. In the last decade, it has taken up new programmes such as adoption of villages and empowerment of rural women, formation of self help groups, encouraging skill training and vocational courses, starting a legal cell, initiating projects in rural sanitation, clean water, and waste management, herbal gardens, disaster management, etc. It has conducted courses in retail marketing. Its library now has a research centre, an excellent archival collection and holds book discussions. In 2010, AIWC set up three trusts for literacy, health and old age and elderly care for the underprivileged and economically weaker sections. AIWC is also actively involved in the issue of climate change. Old programmes have continued and expanded. The working women's hostel at 6 Bhagwan Dass Road continues as does the Bapnu Ghar which provides shelter and counselling to women in distress. Activities in health and family welfare and nonconventional energy also continue. We hope that this edition, like the earlier ones, will be of interest to scholars of history as well as to students of women's studies.